Minimally invasive surgery to the aortic arch – endovascular repair combined with debranching: 4 case reports - Harris, D.G.; Saaiman, A.; du Toit, D.; Rossouw, G. (SA Heart Journal, 2017)
Traditional repair of aortic arch aneurysms requires cardiopulmonary bypass and a period of profound hypothermia and circulatory arrest - allowing detachment of the head vessels off the aneurysm, and their anastomosis onto the graft. The procedure is safe and reproducible, however morbidity is significant and includes air embolism, stroke, excessive bleeding and acidosis. In addition the procedures are time-consuming, and cardioplegic arrest is also necessary, resulting in the potential for low cardiac output. Aortic arch aneurysms are not typically suitable for endovascular intervention. With improving techniques of descending aortic repair with stent grafts, hybrid techniques, which involve aortic arch debranching - thereby creating a proximal landing zone of adequate length, followed by stenting over the aortic arch are becoming popular. Methods: Four cases are presented. The technique involves initial sternotomy or upper sternal split, detachment of the innominate and left common carotid arteries, and their reattachment to the ascending aorta by separate grafts (debranching procedure). During this time a side clamp is placed on the ascending aorta. The left subclavian is usually left intact for technical reasons, unless there is a dominant left vertebral artery. This is safe as the shoulder has adequate collateral circulation, and stenting over this vessel is therefore well tolerated. The aortic arch is then completely covered with a stent graft which is inserted via the femoral artery. Arteriography was performed at the end of the procedure to confirm stent graft position and exclusion of the lesion. Results: All surgical transpositions were successful, and the patients recovered without neurologic, bleeding or cardiac complications. Surgical conversion for aortic graft was never required. There were no endoleaks. Mean duration of follow up was 53.5 months (range 21-77). Conclusions: Endovascular repair of the descending thoracic aorta, initially reserved for inoperable patients, is now becoming the accepted initial management. With improved technology and endografts it is now the safest option, especially for traumatic dissection. These techniques have now extended to the aortic arch. Debranching of the aortic arch enables endovascular grafting in this area, thereby avoiding cardiopulmonary bypass and circulatory arrest. Good pre-operative planning is necessary to make the procedure feasible.